Development of computational methodologies for turbulence transitional flow prediction - Oliveira, Rui Vizinho de (2016)
Turbulence transition modelling is still, albeit the past developments, an active research area of interest for various industry sectors. Its modelling can range from RANS based closures to full DNS computations. The former approach is of course the most feasible simulation methodology. Therefore, RANS based transition models have been developed for industry use. These, range from empirically correlated transition models to physics based phenomenological transition closures. Implementation and validation of these models resulted in a deeper understanding of the processes by which RANS based closures are able to predict turbulence transition onset. The research presented herein on the speci c type of physics in which the transition models are based resulted in an accuracy improvement of an existing turbulence transition closure, the k-kl-!. Additionally, upon gaining a deeper understanding on the role of the pre-transitional ow region, a new turbulence transition model was devised. This is based on a never before applied concept of pre-transitional turbulent vortex deformation due to mean ow shear. This will induce the appearance of a small pre-transitional turbulent viscosity on the edge of the laminar boundary layer. The induced viscosity is a result from the predicted small negative pre-transitional u0v0 values. Although experimentally veri ed, up until now, no model has ever been able to predict this turbulent feature based on a mechanical analogy. The transition V-model was then coupled to a turbulence model, the Spalart-Allmaras closure, resulting in the V-SA transition model. This was validated for a wide range of ow conditions and multiple geometries. It is concluded that the mechanical analogy based closure is a feasible concept with a promising future. Although the developed V-SA turbulence transition model is simple, it is able to predict complex transition phenomenon.